2001
DOI: 10.1046/j.1365-2559.2001.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor expression correlates with tumour grade and vascularity in gliomas

Abstract: These findings support a role for VEGF in the angiogenesis of glioblastoma, anaplastic astrocytoma and oligodendroglioma. The distinct immunoreactivities of the two commercial monoclonal antibodies indicate either there is expression of different splice variants of VEGF or that the epitopes are differentially revealed during synthesis, secretion and receptor-binding of the growth factor. This highlights the importance of using more than one antibody in the evaluation of tissue VEGF expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
3
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 45 publications
(47 reference statements)
10
108
3
10
Order By: Relevance
“…This is consistent with previous work demonstrating that EGFR activation transcriptionally upregulates VEGF expression in GBM cells (Maity et al, 2000). VEGF plays a major role in promoting angiogenesis and tumor growth of GBMs in vivo (Berkman et al, 1993;Cheng et al, 1996;Yuan et al, 1996;Chan et al, 1998;Brat and van Meir, 2001;Chaudhry et al, 2001), and may therefore be critical for EGFR-mediated pathogenesis. This also suggests an important molecular basis on which to select GBM patients for anti-angiogenic therapy.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous work demonstrating that EGFR activation transcriptionally upregulates VEGF expression in GBM cells (Maity et al, 2000). VEGF plays a major role in promoting angiogenesis and tumor growth of GBMs in vivo (Berkman et al, 1993;Cheng et al, 1996;Yuan et al, 1996;Chan et al, 1998;Brat and van Meir, 2001;Chaudhry et al, 2001), and may therefore be critical for EGFR-mediated pathogenesis. This also suggests an important molecular basis on which to select GBM patients for anti-angiogenic therapy.…”
Section: Discussionsupporting
confidence: 91%
“…38,39 In human gliomas, however, both factors are expressed at increased levels that correlate with the grade of malignancy. 4,10,38 We investigated the underlying mechanism of the functional relationship between IL-6 and VEGF in glioma angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of a VEGF antisense construct to reduce angiogenicity and tumorigenicity of human U87MG GBM cells suggested that VEGF plays a key role in glioma development. 3 In human brain cancers, a close correlation was found between VEGF expression, tumor vascularization and grade of malignancy, 4 with 95% of GBMs staining positive for VEGF. 5 The signals were localized in both perinecrotic and vital tumor areas suggesting that both hypoxia and other stimuli may control the expression of VEGF in gliomas.…”
mentioning
confidence: 99%
“…GBM are highly vascularized tumors and VEGF is a leading regulator of GBM angiogenesis [49][50][51][52][53][54].…”
Section: Overview Of the Marketmentioning
confidence: 99%